2013
DOI: 10.5539/jas.v5n2p197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Allele Frequencies of Kappa Casein in Egyptian Cattle and Buffalo Using PCR-RFLP

Abstract: Kappa casein (K-Ca) genetic variations affected quality and composition of the milk. Several variants of Kappa casein (K-Ca) gene locus IV have been reported with special interest for the 'B' allele for its relation to the milk protein and fat yields. Genotyping and allelic frequencies of K-Ca among Native Egyptian breeds of cattle and buffalo were the aim of the present study. PCR amplification of DNA isolated from 300 blood samples collected from Holstein and Baladi cattle and buffalo were performed followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…Heterozygous genotype "AB" was the most frequent genotype among all locations with overall value close to one, while the monomorphic genotype "BB" was noticed in extremely low frequency (0.04) and "AA" genotype was absent as shown in Table 7. These findings disagreed with Gouda et al (2013) who reported that 75% of Egyptian buffaloes had the monomorphic "BB" genotype and only 25% of individuals was heterozygotes "AB" with the predominance of "B" allele (0.875) according to PCR-RFLP results of HindIII restriction enzyme. Likewise, Patel et al (2007) concluded that homozygous genotype "BB" (0.968) was the most frequent genotype comparing to "AB" genotype (0.032) in Indian River buffalo bulls and the frequency of "B" allele was (0.984).…”
Section: Allelic and Genotypic Frequencies Of Studied Genescontrasting
confidence: 74%
See 1 more Smart Citation
“…Heterozygous genotype "AB" was the most frequent genotype among all locations with overall value close to one, while the monomorphic genotype "BB" was noticed in extremely low frequency (0.04) and "AA" genotype was absent as shown in Table 7. These findings disagreed with Gouda et al (2013) who reported that 75% of Egyptian buffaloes had the monomorphic "BB" genotype and only 25% of individuals was heterozygotes "AB" with the predominance of "B" allele (0.875) according to PCR-RFLP results of HindIII restriction enzyme. Likewise, Patel et al (2007) concluded that homozygous genotype "BB" (0.968) was the most frequent genotype comparing to "AB" genotype (0.032) in Indian River buffalo bulls and the frequency of "B" allele was (0.984).…”
Section: Allelic and Genotypic Frequencies Of Studied Genescontrasting
confidence: 74%
“…Coincidence with results of HpyCH4IV enzyme, Gouda et al (2013) also found genetic polymorphism in Egyptian buffalo using PCR-RFLP with HindIII restriction enzyme after digesting of 379 bp PCR product of κ-CN gene with "BB" and "AB" genotypes. Similar results were observed in Indian River buffalo bulls (Patel et al, 2007).…”
Section: Detection Of Polymorphism and Genetic Variants Of κ-Cn And β-Lgsupporting
confidence: 71%
“…These data suggested the advantage of the allele A, with its frequency of 83%, while frequency of the B allele was 17%. Gouda and others (Gouda et al, 2013) observed only two genotypes in a population of Holstein cows. The AB genotype was represented by 76% of cows, and the AA genotype was represented by 24% of cows, and the frequencies of the A and B alleles were 62% and 38%, respectively.…”
Section: Genetic Structurementioning
confidence: 91%
“…and dairy products such as cheese, yoghurt, butter and many others, are a rich source of proteins and minerals and hence constitute an important part of human nutrition. Improvement of milk yield and its composition is a primary goal of animal selection in dairy industry (Caroli et al 2009;Gouda et al, 2013). The nutritional and technological quality of milk is influenced by breed, dietary factors (Dewhurst et al, 2006;Chilliard et al, 2007;Gálik et al, 2011;Šimko et al, 2014), environment (Vidra et al, 2000;Šťastná & Šťastný, 2016), health (Šťastná & Šťastný, 2015a, 2015b) and genetic background of the cows (Vidra et al, 2001;Stoop et al, 2009;Marchitelli et al, 2013).…”
Section: Milkmentioning
confidence: 99%
“…For high productive Holstein Friesian breed some authors (Volkandari et al, 2017, Tanaskovska et al, 2016, Khaizaran and Razem, 2014, Dokso et al, 2014, Ren et al, 2011 determined higher frequency of AA genotype than AB and BB genotypes, what is similar to result obtained for Brown Swiss breed. Other authors, as Doosti et al (2011), Gouda et al (2013), Maletić et al (2016) reported for Holstein breed the highest frequency of AB genotype κ-casein.…”
Section: Resultsmentioning
confidence: 77%